Comparative Analysis on History Teachers Attitudes towards Inclusive Education during Pandemic Times: A Survey of DATIS in Surakarta Senior High Schools - Musa Pelu; Isawati Isawati; Nur F Abidin (Indonesian Journal of Social Science Education (IJSSE), 2022)
This article reports history teachers’ attitudes towards inclusive education during pandemic times. The main question addressed in this study is about to what extent the transition of teachers’ attitudes caused by the adaptive learning framework during pandemic times. A qualitative descriptive based on the framework of Differentiated of Attitudes towards Inclusive Education was used as a research method. The research participants were history teachers in the Surakarta area. The data were collected through an online interview. The findings of the research show that the trained-experienced history teachers tend to believe that students with special needs can get more facilities and learning support in special education, especially during the distance and online learning processes. Meanwhile, untrained-inexperienced history teachers tend to doubt that students with special needs education can gain significant improvement in regular classrooms. To a certain degree, it can be perceived as a symptom of new exclusivism during the pandemic time that can be proved by the tendency of trained-experienced history teachers to exclude students with special education needs based on their needs and lack of inclusive learning sources.